2021
DOI: 10.3390/pathogens10020184
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology Surveillance of SARS-CoV-2: Mutations and Genetic Diversity One Year after Emerging

Abstract: In December 2019, the first cases of the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) were identified in the city of Wuhan, China. Since then, it has spread worldwide with new mutations being reported. The aim of the present study was to monitor the changes in genetic diversity and track non-synonymous substitutions (dN) that could be implicated in the fitness of SARS-CoV-2 and its spread in different regions between December 2019 and November 2020. We analyzed 2213 complete genomes from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 69 publications
(75 reference statements)
3
27
1
Order By: Relevance
“…The nucleotide diversity sliding window showed that the most diverse regions were located at the ORF1a, ORF3, and N loci (Fig. 1 ), agreeing with previous reports [ 59 ]. The viral populations from Peru, Argentina, and Suriname had the highest nucleotide diversity in SA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The nucleotide diversity sliding window showed that the most diverse regions were located at the ORF1a, ORF3, and N loci (Fig. 1 ), agreeing with previous reports [ 59 ]. The viral populations from Peru, Argentina, and Suriname had the highest nucleotide diversity in SA.…”
Section: Discussionsupporting
confidence: 91%
“…Although nucleotide polymorphism (or Watterson estimator θ W ) was considered the best estimator of SARS-CoV-2 diversity [ 57 ], the nucleotide diversity (π) is a better estimator, since it considers the Ss frequency, and it is not influenced by the sample size. The nucleotide diversity in SA (π = 0.00028) was lower than in other continents/countries (Africa, π = 0.00047; Oceania, π = 0.00046; United States of America, π = 0.00044; Europe, π = 0.00043; Asia, π = 0.00042 [ 59 ]). All of these values were lower than those observed for other human viruses (H1N1 = 0.004-0.012 [ 60 , 61 ]; H3N2 = 0.004 [ 60 ]; hepatitis B virus = 0.015 [ 62 ]; parainfluenza virus = 0.002 [ 63 ]), which could be due to the fact that SARS-CoV-2 is a new human virus.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies (one bigdata analysis [50] and two clinical studies [17,51]) reported that the SARS-CoV-2 variants were significantly associated with decrease in severity of disease. The remaining 27 studies (one animal study [18], 22 bigdata analyses [8][9][10][11][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] and four clinical studies [70][71][72][73]) described the positive association between the different variants with severity of COVID-19 (Table 3). A clinical study by Long et al showed that infection with SARS-CoV-2 variants harboring the D614G substitution was not associated with disease severity, overall mortality, transfer to ICU, mechanical ventilation and length of stay at hospital [41].…”
Section: Relation Between Viral Mutations and Severity Of Covid-19 Infectionmentioning
confidence: 99%
“…Since its first detection at Wuhan in China, SARS-CoV-2 (novel coronavirus 2019) has engulfed the world with rapidly accumulating mutations and variants emerging at frequent intervals [1]. More than 100 million infections and 2.4 million deaths have been reported to the World Health Organization [2].…”
Section: Introductionmentioning
confidence: 99%